STRUKTUR KALIMAT KOMPLEKS DALAM BAHASA ARAB: ANALISIS KLAUSA SUBORDINATIF DAN KOORDINATIF - Muammira Enemsaini; Hamzah (Universitas Muhammadiyah Makassar, 2026)
Abstract: Complex sentence structures in Arabic (jumlah murakkabah) represent one of the most intricate dimensions of Arabic grammar, yet they remain underexplored in terms of syntactic typology, particularly concerning the distinction and interaction between subordinate and coordinate clauses. This study aims to describe and analyze the forms, functions, and syntactic markers of subordinate and coordinate clauses in Arabic, as well as to examine their role in constructing meaning within classical and contemporary Arabic texts. Employing a qualitative descriptive approach through content analysis of three selected corpora Quranic verses, classical Arabic prose (nathr), and contemporary Arabic journalistic texts this study analyzes 347 complex sentences using referential and distributional methods. The results indicate that subordinate clauses fall into four main types: relative, nominal, conditional, and adverbial clauses; while coordinate clauses are constructed through conjunctions wa, fa, thumma, and aw, each carrying distinct semantic implications. The study also identifies clause-embedding phenomena reaching three to four layers, far deeper than typically described in standard grammar texts. These findings contribute theoretically to Arabic linguistics and carry practical implications for Arabic language pedagogy at the higher education level. Keywords: Arabic Language; Coordinate Clause; Subordinate Clause; Complex Sentence; Arabic Syntax